The Brand Image and Brand Associations of Langkawi and Phuket: A Brand Concept Map Analysis/ Imej dan Asosiasi Jenama Langkawi dan Phuket: Satu Analisis Peta Konsep Jenama (Sains Humanika, 2020)
In the current competitive scenario of tourism industry, brand association studies are important to identify the authentic brand image of tourism destinations. This would eventually benefit the key players in the tourism industry in planning an effective tourism marketing campaign.Â  The present study aims to analyze the brand image of Langkawi and Phuket and to identify the differences in brand associations in the tourists' memory who visited the two destinations. Incorporating Brand Concept Mapping approach, the study used preliminary survey and focus group interviews to achieve the objectives of the study. Findings indicated that Langkawi was identified as a 'Family-orientedâ€ or â€œMultiproductâ€ Destination as reflected in its multifarious list of brand associations covering from history, natural beauty, shopping centre and recreational destination. Meanwhile, Phuket was associated as an â€˜Entertainment-oriented Destinationâ€™ with its structural brand associations were linked towards entertainment and pleasure such as nightclubs. Thai girl show, brothels and nightlife.
Keywords: Brand concept map; brand image; brand association; Langkawi; Phuket